Flexible transparent conductive polymer film suitable for curved display screen and preparation process of flexible transparent conductive polymer film

By combining the silver ammonia solution of the silver nano -wire combined with hydrophilic flexible polymer base, the silver nano particles generated in situ are mixed in the silver nano wire, which solves the lack of flexibility in the application of the curved screen in the application of the curved screen. The problem of durability realizes the high -conductive and bent -resistant flexible transparent conductive polymer film.

CN119340027AActive Publication Date: 2025-01-21FUJIAN WIWO ELECTRONIC TECH CO LTD
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411565595.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-05
Publication Date
2025-01-21
Estimated Expiration
2044-11-05

AI Technical Summary

Technical Problem

The existing indium tin oxide conductive film lacks flexibility in curved screen applications, which is prone to cracks and fragile. In the conductive network composed of silver nanowires, the contact resistance is large and the heat conduction is poor, which affects the durability of the film.

Method used

By compounding the silver ammonia solution of the silver nanowine and combined with the base of the hydrophilic flexible polymer, the silver nano particles generated in situ are mixed with the silver nano wire, and the conductivity and adhesion of the conductive layer are improved.

Benefits of technology

The conductivity and adhesion of the conductive layer are improved, the patience of the bending is enhanced, the resistance is reduced, and the manufacturing cost is reduced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119340027A_ABST
    Figure CN119340027A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of conductive film preparation, and particularly relates to a flexible transparent conductive polymer film suitable for a curved display screen and a preparation process thereof, and the preparation process comprises the following steps: S1, preparing a silver ammonia solution containing silver nanowires; s2, the silver ammonia solution containing the silver nanowires forms a film on a hydrophilic flexible polymer substrate; and S3, carrying out reduction treatment on the film obtained in the step S2 to obtain the silver nanoparticle and silver nanowire composite flexible transparent conductive polymer film. The silver-ammonia solution of the silver nanowires is compounded, the hydrophilic flexible polymer substrate is combined, the in-situ generated silver nanoparticles are doped in the silver nanowires, and the effect of connecting the silver nanowires and the substrate is achieved at the same time, so that the conductivity and adhesion fastness of the conductive layer are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of conductive film preparation, and in particular relates to a flexible transparent conductive polymer film suitable for a curved display screen and a preparation process thereof. Background Art

[0002] Flexible electronics have become crucial in the development of efficient and stretchable optoelectronic devices such as organic light-emitting diodes, touch screens, e-readers, e-paper, and organic photovoltaic devices. The basic component of flexible electronics is transparent conductive film, which is a thin film material with high transmittance and excellent conductivity in the visible light range. Curved screens are optical devices with a certain curvature, so they need to have good flexibility. Indium tin oxide conductive film (ITO) is the main material used to produce transparent conductive films, but indium tin oxide lacks flexibility, is prone to cracks under repeated bending, and is fragile, which limits its application in the field of curved screens.

[0003] Flexible transparent conductive films made of one-dimensional nanowire materials such as silver nanowires or carbon nanotubes have better photoelectric and bendable properties than ITO films, and the material sources are wide, and large-size, low-cost preparation can be achieved by solution method, which is expected to be widely used in flexible electronic devices. However, in the conductive network composed of silver nanowires, the nanowires overlap each other, resulting in a large resistance at the contact point. At the same time, the heat generated at the overlap can only be conducted along the nanowires. When the power of the heating film is too high, the nanowires will be destroyed, causing the heating film to fail. Patent CN106782769A discloses a flexible transparent conductive composite film with low roughness and low square resistance and a preparation method thereof. The film is a three-layer composite structure, the bottom layer is a transparent polymer film, the middle layer is a conductive network composed of metal nanowires, and the top layer is a transparent conductive layer uniformly covered on the transparent polymer film and the conductive network. Although the roughness and square resistance are reduced, the manufacturing cost is increased. Therefore, it is necessary to provide a new flexible transparent conductive polymer film suitable for curved display screens and a preparation process thereof to solve the above problems. Summary of the invention

[0004] The purpose of the present invention is to provide a flexible transparent conductive polymer film suitable for curved display screens and a preparation process thereof, by compounding a silver ammonia solution of silver nanowires and combining them with a hydrophilic flexible polymer substrate, using in-situ generated silver nanoparticles to dope the silver nanowires, and at the same time playing a role in connecting the silver nanowires and the substrate, thereby improving the conductivity and adhesion strength of the conductive layer.

[0005] To achieve the above object, the present invention provides a process for preparing a flexible transparent conductive polymer film suitable for a curved display screen, comprising the following steps:

[0006] S1, preparing a silver ammonia solution containing silver nanowires;

[0007] S2, forming a film of the silver ammonia solution containing silver nanowires on a hydrophilic flexible polymer substrate;

[0008] S3, performing reduction treatment on the film obtained in step S2 to obtain a flexible transparent conductive polymer film composited with silver nanoparticles and silver nanowires.

[0009] Furthermore, the concentration of the silver ammonia solution is 0.01-0.5 mol / L, and the mass ratio of the silver nanowires to the silver ions in the silver ammonia solution is (1.5-4):1, preferably 2-3:1.

[0010] Furthermore, the silver nanowire has a diameter of 20-30 nm and a length of 20-30 μm.

[0011] Furthermore, the hydrophilic flexible polymer substrate is an acrylic modified polysiloxane substrate.

[0012] Furthermore, the preparation method of the acrylic modified polysiloxane substrate is: grafting polyvinyl siloxane with acrylic acid to obtain acrylic modified polysiloxane, dissolving the acrylic modified polysiloxane in chloroform, and then coating the film on a glass substrate to obtain an acrylic modified polysiloxane substrate.

[0013] Furthermore, the vinyl molar content of the polyvinylsiloxane is 4-8%, and the thickness of the acrylic modified polysiloxane substrate is 80-200 μm.

[0014] Furthermore, step S2 comprises: soaking the hydrophilic flexible polymer substrate in a silver ammonia solution containing silver nanowires for 5-15 minutes, then taking it out and drying it to obtain a hydrophilic flexible polymer composite metal film.

[0015] Furthermore, step S3 comprises: immersing the film obtained in step S2 in a reducing solution for reduction treatment, and the silver complex is reduced to silver nanoparticles.

[0016] Furthermore, the reducing solution is a glucose solution.

[0017] The present invention also provides a flexible transparent conductive polymer film suitable for curved display screens obtained by any of the above preparation processes.

[0018] In general, the above technical solution conceived by the present invention has the following technical advantages compared with the prior art:

[0019] 1. The flexible transparent conductive polymer film suitable for curved display screens provided by the present invention is prepared by compounding a silver ammonia solution of silver nanowires and combining it with a hydrophilic flexible polymer substrate, and doping the silver nanowires with in-situ synthesized silver nanoparticles, which simultaneously connects the silver nanowires and the substrate, thereby improving the conductivity and adhesion strength of the conductive layer.

[0020] 2. The present invention makes the conductive network structure more perfect, ensures the load fastness and reduces the resistance by regulating the content of silver nanowires and silver nanoparticles. The carboxyl group of acrylic acid is used to improve the electrostatic adsorption of silver complex ions, so that the silver nanowires and the reduced silver nanoparticles can be relatively regularly distributed at fixed points, and the generated silver nanoparticles have a fixing effect on the silver nanowires. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 The changes of square resistance of Example 1 and Comparative Example 1 with the number of bending times are shown. DETAILED DESCRIPTION

[0022] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0023] The present invention provides a process for preparing a flexible transparent conductive polymer film suitable for a curved display screen, comprising the following steps:

[0024] S1, preparing a silver ammonia solution containing silver nanowires;

[0025] S2, forming a film of the silver ammonia solution containing silver nanowires on a hydrophilic flexible polymer substrate;

[0026] S3, performing reduction treatment on the film obtained in step S2 to obtain a flexible transparent conductive polymer film composited with silver nanoparticles and silver nanowires.

[0027] Through the above technical scheme, the silver nanowires are compounded with a silver ammonia solution and combined with a hydrophilic flexible polymer substrate, and the in-situ generated silver nanoparticles are doped into the silver nanowires, which simultaneously play a role in connecting the silver nanowires and the substrate, thereby improving the conductivity and adhesion strength of the conductive layer.

[0028] The concentration of the silver ammonia solution is 0.01-0.5 mol / L, and the mass ratio of the silver nanowires to the silver ions in the silver ammonia solution is (1.5-4): 1. The relative amounts of the silver nanowires and the silver ammonia solution have a direct impact on the conductivity of the conductive polymer film. By regulating the content of the silver nanowires and silver nanoparticles, the conductive network structure is more perfect, the load fastness can be guaranteed, and the resistance can be reduced.

[0029] The silver nanowire has a diameter of 20-30 nm and a length of 20-30 μm.

[0030] The hydrophilic flexible polymer substrate is an acrylic modified polysiloxane substrate. The carboxyl group of acrylic acid is used to improve the electrostatic adsorption of silver complex ions, so that the silver nanowires and the reduced silver nanoparticles can be relatively regularly distributed at fixed points, and the generated silver nanoparticles have a fixing effect on the silver nanowires.

[0031] The preparation method of the acrylic modified polysiloxane substrate is as follows: polyvinyl siloxane is subjected to a graft reaction with acrylic acid to obtain acrylic modified polysiloxane, the acrylic modified polysiloxane is dissolved in chloroform, and then coated on a glass substrate to form a film to obtain the acrylic modified polysiloxane substrate. The vinyl molar content of the polyvinyl siloxane is 4-8% (the molar amount of the vinyl-containing chain segment in the entire molecular chain), and the molar ratio of the added amount of acrylic acid to the vinyl is (1-1.2):1.

[0032] The thickness of the acrylic modified polysiloxane substrate is 80-200 μm.

[0033] Step S2 comprises: soaking the hydrophilic flexible polymer substrate in a silver ammonia solution containing silver nanowires for 5-15 minutes, then taking it out and drying it to obtain a hydrophilic flexible polymer composite metal film.

[0034] Step S3 includes: soaking the membrane obtained in step S2 in a reducing solution for reduction treatment, and the silver complex is reduced to silver nanoparticles. The reducing solution is a glucose solution.

[0035] The present invention also provides a flexible transparent conductive polymer film suitable for curved display screens obtained by any of the above preparation processes.

[0036] Example 1

[0037] A flexible transparent conductive polymer film suitable for a curved display screen is prepared by the following steps:

[0038] S1. Prepare a silver ammonia solution containing silver nanowires: the concentration of the silver ammonia solution is 0.1 mol / L (in terms of silver content), the mass ratio of the silver nanowires to the silver ions in the silver ammonia solution is 2:1, the diameter of the silver nanowires is 30 nm, and the length is 30 μm.

[0039] S2. A free radical grafting reaction is carried out between polyvinyl siloxane (the molar content of vinyl is 6%) and acrylic acid in the presence of a catalyst (the molar ratio of the added amount of acrylic acid to the vinyl is 1.1:1) to obtain acrylic modified polysiloxane. The acrylic modified polysiloxane is dissolved in chloroform and then coated on a glass substrate to form a film to obtain an acrylic modified polysiloxane substrate with a thickness of 100 μm.

[0040] The acrylic modified polysiloxane substrate was immersed in a silver ammonia solution containing silver nanowires for 10 minutes, then taken out and dried to obtain a hydrophilic flexible polymer composite metal film.

[0041] S3, soaking the film obtained in step S2 in a glucose solution for reduction treatment to obtain a silver nanoparticle and silver nanowire composite flexible transparent conductive polymer film.

[0042] Example 2

[0043] A flexible transparent conductive polymer film suitable for a curved display screen is prepared by the following steps:

[0044] S1. Prepare a silver ammonia solution containing silver nanowires: the concentration of the silver ammonia solution is 0.1 mol / L (in terms of silver content), the mass ratio of the silver nanowires to the silver ions in the silver ammonia solution is 3:1, the diameter of the silver nanowires is 30 nm, and the length is 30 μm.

[0045] S2. A free radical grafting reaction is carried out between polyvinyl siloxane (the molar content of vinyl is 6%) and acrylic acid in the presence of a catalyst (the molar ratio of the added amount of acrylic acid to the vinyl is 1.1:1) to obtain acrylic modified polysiloxane. The acrylic modified polysiloxane is dissolved in chloroform and then coated on a glass substrate to form a film to obtain an acrylic modified polysiloxane substrate with a thickness of 100 μm.

[0046] The acrylic modified polysiloxane substrate was immersed in a silver ammonia solution containing silver nanowires for 10 minutes, then taken out and dried to obtain a hydrophilic flexible polymer composite metal film.

[0047] S3, soaking the film obtained in step S2 in a glucose solution for reduction treatment to obtain a silver nanoparticle and silver nanowire composite flexible transparent conductive polymer film.

[0048] Example 3

[0049] A flexible transparent conductive polymer film suitable for a curved display screen is prepared by the following steps:

[0050] S1. Prepare a silver ammonia solution containing silver nanowires: the concentration of the silver ammonia solution is 0.1 mol / L (in terms of silver content), the mass ratio of the silver nanowires to the silver ions in the silver ammonia solution is 2:1, the diameter of the silver nanowires is 30 nm, and the length is 30 μm.

[0051] S2. A free radical grafting reaction is carried out between polyvinyl siloxane (the molar content of vinyl is 8%) and acrylic acid in the presence of a catalyst (the molar ratio of the added amount of acrylic acid to the vinyl is 1.1:1) to obtain acrylic modified polysiloxane. The acrylic modified polysiloxane is dissolved in chloroform and then coated on a glass substrate to form a film to obtain an acrylic modified polysiloxane substrate with a thickness of 100 μm.

[0052] The acrylic modified polysiloxane substrate was immersed in a silver ammonia solution containing silver nanowires for 10 minutes, then taken out and dried to obtain a hydrophilic flexible polymer composite metal film.

[0053] S3, soaking the film obtained in step S2 in a glucose solution for reduction treatment to obtain a silver nanoparticle and silver nanowire composite flexible transparent conductive polymer film.

[0054] Example 4

[0055] A flexible transparent conductive polymer film suitable for a curved display screen is prepared by the following steps:

[0056] S1. Prepare a silver ammonia solution containing silver nanowires: the concentration of the silver ammonia solution is 0.1 mol / L (in terms of silver content), the mass ratio of the silver nanowires to the silver ions in the silver ammonia solution is 4:1, the diameter of the silver nanowires is 30 nm, and the length is 30 μm.

[0057] S2. A free radical grafting reaction is carried out between polyvinyl siloxane (the molar content of vinyl is 6%) and acrylic acid in the presence of a catalyst (the molar ratio of the added amount of acrylic acid to the vinyl is 1.1:1) to obtain acrylic modified polysiloxane. The acrylic modified polysiloxane is dissolved in chloroform and then coated on a glass substrate to form a film to obtain an acrylic modified polysiloxane substrate with a thickness of 100 μm.

[0058] The acrylic modified polysiloxane substrate was immersed in a silver ammonia solution containing silver nanowires for 10 minutes, then taken out and dried to obtain a hydrophilic flexible polymer composite metal film.

[0059] S3, soaking the film obtained in step S2 in a glucose solution for reduction treatment to obtain a silver nanoparticle and silver nanowire composite flexible transparent conductive polymer film.

[0060] Example 5

[0061] A flexible transparent conductive polymer film suitable for a curved display screen is prepared by the following steps:

[0062] S1. Prepare a silver ammonia solution containing silver nanowires: the concentration of the silver ammonia solution is 0.1 mol / L (in terms of silver content), the mass ratio of the silver nanowires to the silver ions in the silver ammonia solution is 2:1, the diameter of the silver nanowires is 30 nm, and the length is 30 μm.

[0063] S2. Perform free radical grafting reaction of polyvinylsiloxane (vinyl molar content is 4%) and acrylic acid in the presence of a catalyst (the molar ratio of the added amount of acrylic acid to the vinyl group is 1.1:1) to obtain acrylic modified polysiloxane, dissolve the acrylic modified polysiloxane in chloroform, and then apply it on a glass substrate to form a film to obtain an acrylic modified polysiloxane substrate with a thickness of 100 μm.

[0064] The acrylic modified polysiloxane substrate was immersed in a silver ammonia solution containing silver nanowires for 10 minutes, then taken out and dried to obtain a hydrophilic flexible polymer composite metal film.

[0065] S3, soaking the film obtained in step S2 in a glucose solution for reduction treatment to obtain a silver nanoparticle and silver nanowire composite flexible transparent conductive polymer film.

[0066] Comparative Example 1

[0067] A flexible transparent conductive polymer film suitable for a curved display screen is prepared by the following steps:

[0068] S1. Prepare a silver ammonia solution containing silver nanowires: the concentration of the silver ammonia solution is 0.1 mol / L (in terms of silver content), the mass ratio of the silver nanowires to the silver ions in the silver ammonia solution is 2:1, the diameter of the silver nanowires is 30 nm, and the length is 30 μm.

[0069] S2. Scrape polydimethylsiloxane onto a glass substrate to form a film, thereby obtaining a polydimethylsiloxane base with a thickness of 100 μm.

[0070] The polydimethylsiloxane substrate was immersed in a silver ammonia solution containing silver nanowires for 10 minutes, and then taken out and dried to obtain a flexible polymer composite metal film.

[0071] S3, soaking the film obtained in step S2 in a glucose solution for reduction treatment to obtain a silver nanoparticle and silver nanowire composite flexible transparent conductive polymer film.

[0072] The square resistance test of the samples of Examples 1-3 and Comparative Examples 1-3 was performed before and after bending, wherein the bending was performed 50 times with a curvature radius of 2 mm.

[0073] Table 1 Square resistance test results of Examples 1-5 and Comparative Example 1

[0074]

[0075] As can be seen from Table 1, when the silver ammonia solution content is too low, the square resistance increases, and the square resistance change rate after bending is higher, indicating that the generated silver nanoparticles help improve the bending resistance of the conductive layer. When the vinyl content is too low, the grafted carboxyl groups also decrease, which in turn affects the fixed-point generation of silver nanoparticles, increases the square resistance, and deteriorates the bending resistance. Figure 1 It can be seen that after Example 1 was bent 50 times with a curvature radius of 2 mm, the change rate of square resistance was still small, indicating good bending resistance. However, after Comparative Example 1 was bent more than 20 times, the square resistance increased significantly, indicating that when the substrate did not contain acrylic groups, the silver nanoparticles of the silver nanowires were unevenly arranged and the growth of the silver nanoparticles was affected, resulting in a significant decrease in bending resistance.

[0076] It will be easily understood by those skilled in the art that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A process for preparing a flexible transparent conductive polymer film suitable for a curved display screen, characterized in that: The following steps are involved: S1, preparing a silver ammonia solution containing silver nanowires; S2, forming a film of the silver ammonia solution containing silver nanowires on a hydrophilic flexible polymer substrate; S3, performing reduction treatment on the film obtained in step S2 to obtain a flexible transparent conductive polymer film composited with silver nanoparticles and silver nanowires.

2. The process for preparing a flexible transparent conductive polymer film suitable for a curved display screen according to claim 1, characterized in that: The concentration of the silver ammonia solution is 0.01-0.5 mol / L, and the mass ratio of the silver nanowires to the silver ions in the silver ammonia solution is (1.5-4):

1.

3. The process for preparing a flexible transparent conductive polymer film suitable for a curved display screen according to claim 1, characterized in that: The silver nanowire has a diameter of 20-30 nm and a length of 20-30 μm.

4. The process for preparing a flexible transparent conductive polymer film suitable for a curved display screen according to claim 1, characterized in that: The hydrophilic flexible polymer substrate is an acrylic modified polysiloxane substrate.

5. The process for preparing a flexible transparent conductive polymer film suitable for a curved display screen according to claim 4, characterized in that: The preparation method of the acrylic modified polysiloxane substrate is as follows: polyvinyl siloxane is subjected to a grafting reaction with acrylic acid to obtain acrylic modified polysiloxane, the acrylic modified polysiloxane is dissolved in chloroform, and then the acrylic modified polysiloxane is coated on a glass substrate to form a film to obtain the acrylic modified polysiloxane substrate.

6. The process for preparing a flexible transparent conductive polymer film suitable for a curved display screen according to claim 5, characterized in that: The vinyl molar content of the polyvinylsiloxane is 4-8%, and the thickness of the acrylic modified polysiloxane substrate is 80-200 μm.

7. The process for preparing a flexible transparent conductive polymer film suitable for a curved display screen according to claim 1, characterized in that: Step S2 comprises: soaking the hydrophilic flexible polymer substrate in a silver ammonia solution containing silver nanowires for 5-15 minutes, then taking it out and drying it to obtain a hydrophilic flexible polymer composite metal film.

8. The process for preparing a flexible transparent conductive polymer film suitable for a curved display screen according to claim 7, characterized in that: Step S3 comprises: immersing the film obtained in step S2 in a reducing solution for reduction treatment, and the silver complex is reduced to silver nanoparticles.

9. The process for preparing a flexible transparent conductive polymer film suitable for a curved display screen according to claim 8, characterized in that: The reducing solution is a glucose solution.

10. A flexible transparent conductive polymer film suitable for curved display screens obtained by the preparation process according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Low-roughness and low-square-resistance flexible transparent conductive composite thin film and preparation method therefor

    CN106782769A

  • Flexible transparent film electrode and manufacturing method thereof

    CN103871548A

  • Flexible and transparent conductive film and preparation method thereof

    CN104916351A

  • Chemical method for promoting silver nanowire nodes to be welded into continuous low-resistance conductive network

    CN113106430A

  • Flexible silver nanowire-based composite transparent film heater and preparation method thereof

    CN113963844A